Antioxidant, anti-obesity, nutritional and other beneficial effects of different chili pepper: a review - Azlan, Azrina; Sultana, Sharmin; Chan, Suk Huei; Razman, Muhammad Rizal (Multidisciplinary Digital Publishing Institute, 2022)
Fruits and vegetables are important components of a healthy diet. They are rich sources of vitamins and minerals, dietary fibre and a host of beneficial non-nutrient substances including plant sterols, flavonoids and other antioxidants. It has been reported that reduced intake of fruits and vegetables may increase the risk of non-communicable diseases (NCDs). Chili pepper, is a common and important spice used to enhance taste and nutrition. Over the years, reports have shown its potential as antioxidant and an anti-obesity agent. Obesity is a serious health concern as it may initiate other common chronic diseases. Due to the side effects of synthetic antioxidants and anti-obesity drugs, scientists are now focusing on natural products which produce similar effects to synthetic chemicals. This up-to-date review addresses this research gap and presents, in an accessible format, the nutritional, antioxidant and anti-obesity properties of different chili peppers. This review article serves as a reference guide for use of chili peppers as anti-obesity agents.